Short Communication: Population structure of mangrove crab Scylla oceanica in mangrove ecosystem of Tanjung Lesung, Banten, Indonesia - TITING PUDIAWATI; MUFTI P. PATRIA (Biodiversitas Journal of Biological Diversity, 2017)
Pudiawati T, Patria MP. 2017. Short Communication: Population structure of mangrove crab Scylla oceanica in mangrove ecosystem of Tanjung Lesung, Banten, Indonesia. Biodiversitas 18: 813-817. The mangrove crab Scylla oceanica is one of the dominant crabs in the mangrove ecosystem at Tanjung Lesung Beach, Banten, Indonesia. The aim of the study was to determine the temporal distribution, carapace width-weight relationship and condition factors of S. oceanica. The crabs were collected by using traps for four months from August to November 2015. It was observed that the carapace was larger in male crabs (9.97 cm) than in female crabs (9.34 cm) and the average weight of the males (206.08 g) was higher than that of the females (183.83 g). b value of male (1.955) and female (2.123) crabs were significantly different (P < 0.05). Both of them have a negative allometric growth pattern. The result of the distribution analysis was a Morisita spread index Id of 1.5176; this indicates the crabs have clustered distribution patterns and their distribution was allegedly associated with the reproductive cycle.